2021
DOI: 10.1186/s12864-021-07795-9
|View full text |Cite
|
Sign up to set email alerts
|

A functional map of genomic HIF1α-DNA complexes in the eye lens revealed through multiomics analysis

Abstract: Background During eye lens development the embryonic vasculature regresses leaving the lens without a direct oxygen source. Both embryonically and throughout adult life, the lens contains a decreasing oxygen gradient from the surface to the core that parallels the natural differentiation of immature surface epithelial cells into mature core transparent fiber cells. These properties of the lens suggest a potential role for hypoxia and the master regulator of the hypoxic response, hypoxia-inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 135 publications
1
17
0
Order By: Relevance
“…The differentiation state-specific expression patterns of these genes suggests that specific regulatory mechanisms operate to govern their expression levels during lens cell differentiation. Consistently, previous studies have identified multiple transcription factors [ 25 , 28 , 29 , 41 , 44 46 ] required for their differentiation state-specific expression patterns. Recently, epigenetic programming was shown to play an important role in the regulation of gene expression during lens fiber cell differentiation since ATAC (assay for transposase-accessible chromatin) sequencing of undifferentiated lens epithelial and differentiated fiber cells identified genome-wide changes in chromatin accessibility associated with the expression of multiple genes during lens differentiation [ 32 , 47 ].…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…The differentiation state-specific expression patterns of these genes suggests that specific regulatory mechanisms operate to govern their expression levels during lens cell differentiation. Consistently, previous studies have identified multiple transcription factors [ 25 , 28 , 29 , 41 , 44 46 ] required for their differentiation state-specific expression patterns. Recently, epigenetic programming was shown to play an important role in the regulation of gene expression during lens fiber cell differentiation since ATAC (assay for transposase-accessible chromatin) sequencing of undifferentiated lens epithelial and differentiated fiber cells identified genome-wide changes in chromatin accessibility associated with the expression of multiple genes during lens differentiation [ 32 , 47 ].…”
Section: Introductionsupporting
confidence: 87%
“…7 A, Additional file 13 : Table S9A). Many of the enriched binding motifs are from transcription factors with well-established roles in regulation of lens gene expression, lens development, and differentiation (Additional file 13 : Table S9) [ 44 , 64 , 67 89 ]. Consistently, previous studies showed HIF1 to be a major regulator of lens gene expression [ 44 ], RBPJ is involved in early lens development [ 64 , 87 ], and both c-Myc and n-Myc have established roles in lens cell proliferation and differentiation [ 70 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations